Trends and practices in prescribing anti-psychotropic medications in hospitalized patients with psychiatric disorders in a secondary care hospital - Shareef, Javedh; Rao, Padma G. M.; Ayman, Itaf Mohamad (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Advances in the psycho-pharmacotherapy enhance the development of newer and better drugs in the management of psychiatric disorders. However, their proper utilization, safety and efficacy and adverse effects in the clinical practice needs continuous study. The study aimed to assess the trends and practice of prescribing psychotropic medications in hospitalized patients in a secondary care hospital in Ras Al Khaimah. Methods: A prospective observational study was carried out for a period of six months in a psychiatry department. All the patient details including the demographic data and prescribing pattern of antipsychotic medication were collected from the patient case records and were later analysed by using descriptive statistics. Results: A total of 50 patient’s prescription were analysed during the study period. Male (54%) predominance was noted over females (46%) with majority (64%) of patients were in the age group of 21-40 years. Schizophrenia (35.8%) was the most common psychiatric disorders followed by affective disorders (30.86%). The average number of psychiatric drugs per prescription was found to be 3.38±1.23. Antipsychotics (43.36%) were the commonly prescribed class of medications followed by mood stabilizers (12.38%) and anxiolytics (11.06%) with olanzapine (n=26), sodium valproate (n=21) and clonazepam (n=9) being frequently prescribed medications. Escitalopram (n=9) was the most commonly used anti-depressants. Combination therapy (86%) is preferred over monotherapy (14%). Conclusions: This study helps to assist in ensuring rational drug therapy and reducing the incidence of drug related problems and medication errors and thereby enhancing the quality of care in patients with psychiatric disorders.